4,4′-Di-tert-butyl-6-(1H-tetrazol-5-yl)-2,2′-bipyridine: modification of a highly selective N-donor ligand for the separation of trivalent actinides from lanthanides - Maiwald, Martin M.; Skerencak-Frech, Andrej; Panak, Petra (Dalton transactions, 2017)
In the present work, the complexation and extraction behaviour of 4,4′di-tert-butyl-6-(1H-tetrazol-5-yl)-2,2′-bipyridine (HN4tbubipy) towards trivalent actinides (An(III)) and lanthanides (Ln(III)) is studied by spectroscopic methods, liquid-liquid extraction, and quantum chemical calculations. The ligand synthesis of HN4tbubipy as well as its application in coordination chemistry of the 4f elements is described. Reaction of HN4tbubipy with [Ln(NO3)3·6H2O] (Ln = Sm, Eu) results in [H2N4tbubipy]+[Ln(N4tbubipy)(NO3)3(H2O)]−. Both compounds have been characterized by single crystal X-ray diffraction. The solubility of the ligand in different organic solvents is determined, showing a high solubility in MeOH which decreases with the lipophilicity of the solvent. The pKa = 2.4 ± 0.2 of HN4tbubipy in EtOH (4.4 vol% H2O) is determined by absorption spectrophotometry. The complexation of Cm(III) and Eu(III) with HN4tbubipy is studied by time resolved laser fluorescence spectroscopy (TRLFS). For both metal ions the formation of the complexes [M(N4tbubipy)n]3−n with n = 2, 3 (M = Cm(III), Eu(III)) is observed. Slightly higher conditional stability constants for Eu(III) (log β′2(Eu(N4tbubipy)2+) = 8.9 ± 0.3, log β′3(Eu(N4tbubipy)3) = 12.7 ± 0.5), compared to Cm(III) (log β′2(Cm(N4tbubipy)2+) = 8.5 ± 0.4 and log β′3(Cm(N4tbubipy)3) = 12.4 ± 0.6) are determined. Thus, the ligand has no preference for the complexation of An(III) over Ln(III). Additionally, no significant extraction of Am(III) and Eu(III) is observed in liquid-liquid extraction experiments due to protonation of the ligand at the experimental conditions. The experimental studies are supported by quantum chemical calculations of the free ligand and the [M(N4tbubipy)3] complexes (M = Cm(III), Gd(III)). The results are in excellent agreement with the experimental data and provide a deeper understanding of the complexation properties of HN4tbubipy.